Statistical mechanics selecta of Elliott H Lieb - Nachtergaele B; Solovej J P ed.; Yngvason J (Berlin Springer-Verlag, 2004)
In Statistical Physics one of the ambitious goals is to derive rigorously, from statistical mechanics, the thermodynamic properties of models with realistic forces. Elliott Lieb is a mathematical physicist who meets the challenge of statistical mechanics
Keywords: Statistical mechanics